Analysis of the effect of age and residence on the incidence of Giant Cell Tumors - Kurniati, Yuni Prastyo; Zahro, Ikhya' Izatus; Romadhon, Yusuf Alam (Universitas 'Aisyiyah Yogyakarta, 2023)
Giant cell tumors are benign neoplasms that damage bone and often recur and have aggressive lesions. Benign tumors that can transform into malignant, aggressive, and able to metastasize to other organs.These tumors range from 3-8% of primary bone tumors in Western populations and as many as 20% in Asian countries. Risk factors for this disease are more common in women and at the age of the second to fourth decade. However, there are differences about the distribution of rural and urban areas between countries, as well as the age distribution of patients with these tumors in some countries. The purpose of this study was to analyze the effect of age and residence on the occurrence of Giant Cell Tumor. This study used a cross-sectional research design. The study sample was a histopathology preparation taken from 107 patient medical record data according to inclusion criteria using purposive sampling techniques. The results of the study found subjects with the most GCT were found in the high-risk age group (age range 20 to 50 years) of 67.3% and most of them lived in urban areas as much as 81.3%. Fisher's test showed an influence of age on the incidence of giant cell tumors (p = 0.007) and no influence between residence and the incidence of giant cell tumors (p = 0.262). The conclusion of this study is that age has a significant effect on the occurrence of Giant cell tumors. Meanwhile, residence does not affect the occurrence of Giant cell tumors.